Prevalence and prognostic value of PD-L1 expression in molecular subtypes of metastatic large cell neuroendocrine carcinoma (LCNEC). (April 2019) - Hermans, B.C.M.; Derks, J.L.; Thunnissen, E.; van Suylen, R.J.; den Bakker, M.A.; Groen, H.J.M.; Smit, E.F.; Damhuis, R.A.; van den Broek, E.C.; Stallinga, C.M.; Roemen, G.M.; Speel, E.J.M.; et al.
Highlights: PD-L1 ≥ 1% is expressed in 16% of stage IV LCNEC, 5% has expression ≥50%. PD-L1 staining in LCNEC is comparable to values in SCLC, but lower than in NSCLC. No difference in PD-L1 expression is found in RB1 mutated and RB1 wildtype subgroups. Expression of PD-L1 (tumor cells) and CD8 (tumor infiltrating cells) is associated. Overall survival is prolonged in patients with PD-L1+ and CD8+ LCNEC. Abstract: Background: Pulmonary large cell neuroendocrine carcinoma (LCNEC) is a rare tumor with high mutational burden. Two subtypes of LCNEC are recognized, the co-mutated TP53 and RB1 group and the TP53 and STK11/KEAP1 group. We investigated PD-L1 and CD8 expression in a well characterized stage IV LCNEC cohort and compared expression in the two subtypes. Methods: Immunohistochemical (IHC) analysis for PD-L1 and CD8 was performed on pathological reviewed pretreatment tumor samples for 148 stage IV LCNEC. Data about targeted next generation sequencing (TNGS) ( TP53, RB1, STK11, KEAP1) and IHC for RB1 were available for most tumors. IHC staining for PD-L1 (DAKO 28-8) was performed and scored positive if tumors showed ≥1% membranous staining. CD8 was scored for intra-tumor T-cells and stromal cells. Results: PD-L1 IHC expression data could be generated in 98/148 confirmed LCNEC samples along with RB1 IHC (n = 97) of which 77 passed quality control for TNGS. PD-L1 expression was positive in 16/98 cases (16%); 5 (5%) with ≥50%. PD-L1 expression was equal in RB1 mutated and RB1 wildtype tumors. None of STK11 mutated tumors (n = 7) expressed PD-L1. PD-L1 expression was correlated with superior overall survival (OS), hazard ratio 0.55 ((95% Confidence Interval 0.31-0.96), p = 0.038). Intra-tumor CD8 was associated with PD-L1 expression (p = 0.021) and stromal and intra-tumor CD8 were correlated with improved OS (p = 0.037 and p = 0.026 respectively). Conclusions: PD-L1 expression was positive in 16% of stage IV LCNEC tumors. This was independent of molecular subtype but associated with CD8 expression. In LCNEC patients with PD-L1 and/or CD8 expression superior OS was observed.